2015
DOI: 10.3233/jad-150555
|View full text |Cite
|
Sign up to set email alerts
|

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer’s Disease Risk in APOE ɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium

Abstract: The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 40 publications
6
33
0
Order By: Relevance
“…In the present study, we find significant risk associations in our independent FTD and PSP-S cohorts with the p.A152T variant. This replicates the effect for FTD we reported initially (Coppola et al , 2012) and is consistent with the trend observed by Pastor et al (2016). Thus, we feel that this constitutes good genetic support for p.A152T as a tauopathy risk variant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we find significant risk associations in our independent FTD and PSP-S cohorts with the p.A152T variant. This replicates the effect for FTD we reported initially (Coppola et al , 2012) and is consistent with the trend observed by Pastor et al (2016). Thus, we feel that this constitutes good genetic support for p.A152T as a tauopathy risk variant.…”
Section: Discussionsupporting
confidence: 91%
“…After the initial study that reported significant risks for p.A152T carriers to develop Alzheimer’s disease and FTD spectrum disorders (Coppola et al , 2012), Labbe et al (2015) reported significant associations with cohorts with clinically-diagnosed or pathologically-confirmed dementia with Lewy bodies. However, Pastor et al (2016) did not show a significant association between p.A152T and Alzheimer’s disease, and the association with FTD was of borderline significance (OR = 2.03; 95% CI = 0.95–4.34 P = 0.063) (Pastor et al , 2016). …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The extent of LD in the MAPT region poses great difficulty in discerning the gene(s) and functional variants that impose risk for PSP and other neurodegenerative diseases that associate with SNPs in this region, such as Alzheimer’s (AD)[24,31,1] and Parkinson’s disease(PD)[11,40]. The hallmark of tau pathology in AD, PSP and other tauopathies and presence of deterministic MAPT mutations that lead to neurodegeneration (reviewed[17]) strongly implicate MAPT as the culprit in these disease associations.…”
Section: Discussionmentioning
confidence: 99%
“…37 Another study found an increased risk of clinical AD for carriers of MAPT H1 haplotype, but only in APOE ε4-negative strata. 38 The current study found changes in MAPT to be associated with altered risk of cognitive symptoms, primarily driven by altered risk in the APOE ε4-positive strata.…”
Section: Discussionmentioning
confidence: 50%